Triptofan in njegova vloga v človeškem organizmu - Dolšak, Ana (Farmacevtski vestnik, 2023)
Tryptophan represents one of the 20 amino acids for humans and is consumed through a balanced diet. In addition to its structural role as a building block of proteins it serves as a precursor to many biologically active molecules, indirectly influences sleep and wellbeing, and plays an important role in regulating the immune system. Deficiency occurs very rarely; however, it could be used as a dietary supplement to improve mood and sleep quality. Metabolism occurs through the serotonin or kynurenine pathway, and the resulting metabolites may be involved in various diseases, such as cancer, autoimmune diseases, inflammation and infections. Therefore, the enzymes involved in tryptophan metabolism represent potential targets for the development of new drugs.
Keywords: bolezenska stanja; Metabolizem; Prehranska dopolnila; terapevtska uporaba; triptofan